2013
DOI: 10.1007/s00394-013-0516-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate attenuates fibrosis, oxidative stress, and inflammation in non-alcoholic fatty liver disease rat model through TGF/SMAD, PI3 K/Akt/FoxO1, and NF-kappa B pathways

Abstract: Epigallocatechin gallate (EGCG) reduced the severity of liver injury in an experimental model of NAFLD associated with lower concentration of pro-fibrogenic, oxidative stress, and pro-inflammatory mediators partly through modulating the activities of TGF/SMAD, PI3 K/Akt/FoxO1, and NF-κB pathways. Therefore, green tea polyphenols and EGCG are useful supplements in the prevention of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 42 publications
10
129
0
Order By: Relevance
“…In this investigation, to imitate the clinical scenario of RA, CIA was induced in Lewis rats and subsequently, the anti-arthritic potency of Camellia sinensis stew was assessed in mentioned experimental model. This beverage is being used for many years and possesses antioxidant activities, anti-inflammatory, anti-apoptotic properties and protective effects in autoimmune animal models [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, to imitate the clinical scenario of RA, CIA was induced in Lewis rats and subsequently, the anti-arthritic potency of Camellia sinensis stew was assessed in mentioned experimental model. This beverage is being used for many years and possesses antioxidant activities, anti-inflammatory, anti-apoptotic properties and protective effects in autoimmune animal models [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, it has been shown that EGCG inhibits the PI3K/Akt system in fibroblast cells (12) and the phosphorylation of ERK and Akt kinases in epidermal growth factor (EGF)-stimulated cells (13). More recently, accumulating evidence indicates that EGCG can inhibit PI3K/Akt and MAPK signaling systems (14)(15)(16)(17).…”
Section: Abstract Background/aim: (-)-Epigallocatechin-3-gallate (Egmentioning
confidence: 99%
“…Effect of rapamycin on P-gp expression in HepG2 cells exposed to DOX. Recently, it has been indicated that EGCG has an inhibitory property against mTOR, as well as PI3K (17). Therefore, we investigated the effect of rapamycin on P-gp level as this agent inactivates mammalian target of ANTICANCER RESEARCH 37: 6071-6077 (2017) 6074 Figure …”
Section: Effects Of Egcg and Dox On The Phosphorylation Of Akt Erk1/mentioning
confidence: 99%
“…Both in vitro and in vivo experiments have revealed that green tea and EGCG could prevent steatosis by reducing dietary absorption of lipids and carbohydrates, and by the inhibition of adipose tissue breakdown, and de novo lipogenesis in both hepatic and adipose tissues, through the stimulation of β-oxidation and thermogenesis in the liver, and by improving insulin sensitivity. Furthermore, EGCG may inhibit the development of steatohepatitis from fatty liver disease, through its antioxidant and antiinflammatory characteristics [47] . Currently, there are no randomized, controlled trials in humans, evaluating the effects of green tea on NAFLD.…”
Section: Green Tea Extractmentioning
confidence: 99%